Synthesis and characterization of Co-W alloy coatings for enhanced hydrogen evolution: effects of bath composition and deposition parameters - A. Chitharanjan Hegde; Meghana K. Navada; Ganesha Aroor; Akshatha R. Shetty (Arab Journal of Basic and Applied Sciences)
This study explores the development of Co-W alloy coatings as efficient electrode materials for the hydrogen evolution reaction (HER), offering new insights into their performance. Using a specially formulated electrolyte bath with glycerol as an additive, Co-W alloy coatings were deposited on copper under different [Co2+]/[WO42−] molar ratios. Their electrocatalytic efficiency was evaluated in 1 M KOH through cyclic voltammetry (CV), chronopotentiometry (CP), and hydrogen gas measurements using a custom glass device. The results showed that the combination of Co and W in the coatings significantly enhances performance, as confirmed by SEM, XRD, and EDS analyses. Potentiodynamic polarization studies further explained the HER mechanisms. This work introduces a unique bath composition and demonstrates how optimizing the alloy composition can improve HER activity, paving the way for better electrocatalysts. The study identified that the Co-W coating prepared using a 0.35 M solution at a current density of 1 Adm2 demonstrated the highest electrocatalytic efficiency. This performance was attributed to the tungsten content of approximately 30 wt% and the maximum hydrogen evolution observed under these optimized conditions. The hydrogen evolution reaction (HER) in Co-W alloys follows the Volmer-Heyrovsky mechanism, characterized by the rapid evolution of hydrogen.